The Role Of Product Quality, Brand Image, And Word Of Mouth In Enhancing Purchase Decisions And Customer Satisfaction In Tiktok Live Commerce - Dea, Dea Aditia Maharani; Prastowo, Sugeng Lubar (IJBLE Scientific Publications Community Inc., 2025)
This study investigates the influence of live streaming, product quality, and word of mouth (WOM) on customer satisfaction, with brand image and purchase decision as mediating variables among Sattka hijab consumers on TikTok Shop. Live commerce has grown rapidly, yet prior research has reported inconsistent findings regarding its determinants of satisfaction and purchase decisions. Using a quantitative approach with 200 respondents and Structural Equation Modeling (SEM-PLS), this study reveals that product quality, brand image, and WOM have significant positive effects on purchase decisions, which in turn enhance customer satisfaction. Conversely, live streaming does not significantly influence brand image, highlighting that product quality and brand reputation are stronger predictors of consumer behavior than promotional intensity through live streaming. These findings underscore the importance of prioritizing product excellence and reputation management in shaping long-term consumer satisfaction and loyalty in live commerce settings.